Analysis of factors affecting development inequality in East Java Province 2015-2019 - Dian Fatmala; Sugeng Hadi Utomo (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2022)
Abstract One indicator of community welfare in an area is the increase in GRDP per capita. However, if the increase in GRDP is not balanced with equitable development, it will cause development inequality problems. This study describes development inequality in districts/cities in East Java using the Williamson Index. The purpose of this study is to explore the conditions of development inequality in districts/cities in East Java with the Williamson Index and its influencing variables. This study uses panel data regression analysis from 38 provinces in Indonesia for 5 years. The secondary data used were in the form of GRDP and population data in 38 regencies/cities, Locally Generated Revenue data, HDI, and Workforce in each Regency/City in East Java from 2015-2019. These panel data were then processed using Ms. Excel and Eviews10. The results of this study indicate that the level of inequality in East Java has increased every year. GRDP and LFPR have a positive effect, while Locally Generated Revenue and HDI have a negative effect. Variables that have a significant effect on alpha 0.05 or 5% are GRDP and HDI. While Locally Generated Revenue and TPAK are at a significance level of more than alpha 0.05 Abstrak Salah satu indikator kesejahteraan masyarakat di suatu daerah adalah peningkatan PDRB per kapita. Namun, jika peningkatan PDRB tidak diimbangi dengan pemerataan pembangunan, maka akan menimbulkan masalah ketimpangan pembangunan. Penelitian ini menggambarkan ketimpangan pembangunan di kabupaten/kota di Jawa Timur dengan menggunakan Indeks Williamson. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana kondisi ketimpangan pembangunan di kabupaten/kota di Jawa Timur dengan Indeks Williamson dan apa saja variabel-variabel yang mempengaruhinya. Penelitian ini menggunakan analisis regresi data panel dari 38 provinsi di Indonesia selama 5 tahun. Data sekunder yang digunakan berupa data PDRB dan jumlah penduduk di 38 kabupaten/kota, data Pendapatan Asli Daerah, IPM, Angkatan Kerja di setiap Kabupaten/Kota di Jawa Timur selama tahun 2015-2019 yang kemudian data panel tersebut diolah dengan menggunakan Ms. Hasil dari penelitian ini menunjukkan bahwa tingkat ketimpangan di Jawa Timur mengalami peningkatan setiap tahunnya. PDRB dan LFPR berpengaruh positif, sedangkan Pendapatan Asli Daerah dan IPM berpengaruh negatif. Variabel yang berpengaruh signifikan pada alpha 0,05 atau 5% adalah PDRB dan IPM. Sedangkan PAD dan TPAK berada pada tingkat signifikansi lebih dari alpha 0,05